A JOURNEY TO GOD : REFLECTIONS ON THE HIKAM OF IBN ATA'ILLAH - Auda, Jasser (Awakening Publications, 2017)
The ultimate yearning of the human soul is to return to its Lord in a state where He is pleased with His servant and the Servant is pleased with his Master. This book offers a unique insights to prepare you for the journey to God through the wisdom of the great spiritual master Ibn Ata'illah al-Iskandari as expounded in his masterpiece al-Hikam.